Implementasi Metode Technique for Order Preference by Similarity to Ideal Solution dalam Pemilihan Jenis Kerang Konsumsi - Siregar, Kristian; Siagian, Edward Robinson (MEANS (Media Informasi Analisa dan Sistem), 2018)
Shellfish is a type of seafood consumed by consumers. In selecting the right type of shellfish, it must be adjusted to the wishes of consumers. To get optimal results a system is needed that can help in determining the type of shellfish so that consumers feel satisfied. Technique for Order Preference by Similarity to Ideal Solution or TOPSIS is a method with the concept that each alternative is chosen and the best is not only to have the shortest distance of each positive ideal solution, but also to have the longest distance of any existing ideal negative solution . The criteria in this system vary, each tailored to the preferences of consumers or prospective buyers of shellfish provided by the producer. Based on the results of the sample selection shows that the calculation results using the same system with manual calculations. This system is able to provide an election for purchasing shellfish.